A tentative model on effective army combat tactics. Issue 5 (2nd September 2020) - Thunholm, Peter; Henåker, Lars
Abstract: The purpose of this study is to form a model on effective tactics. We selected five theorists, three of which also provided support from quantitative analysis on winning battles. The theorists all advocate the use of maneuver warfare, developed from the German WWII-approach. The analysis indicates the importance of accomplishing a sequence in battle of surprise attacks, followed by shock action, and prompt exploitation in order to accomplish an organizational breakdown of enemy force. Tactical defeat is foremost a result of psychological reactions by the enemy rather than from physical destruction by superior material resources at the point of assault.